HUBUNGAN KUALITAS PELAYANAN KESEHATAN DENGAN KEPUASAN PASIEN BPJS - Nordianiwati, Nordianiwati; Putri, Puput; Kadir, Abd; Millati, Rida' (Ensiklopedia of Journal, 2025)
Abstract: Hospitals are one of the health facilities that have a very important role in providing nursing services and various other types of health services at various levels of society. Implementation of BPJS Health, in its implementation is still inadequate. The purpose of the study was to determine the relationship between the quality of health services and BPJS patient satisfaction. The research design used in this study was cross sectional. The research was conducted at the Sultan Agung Islamic Hospital Semarang. The research was conducted in April 2024. The study population was inpatients in Baitussalam 1 and 2, Baitunnisa 1 and 2. The sample amounted to 92 people. The sampling technique used purposive sampling. Data analysis was carried out univariate and bivariate. The results showed that there was a relationship between health services and patient satisfaction who received BPJS Health services with a p value: 0.035. It is recommended that the hospital can be information, so that it will be easy if you want to improve the quality of health services.Keywords: Patient, Health Care. Hospital.